2021
DOI: 10.1371/journal.pone.0255233
|View full text |Cite
|
Sign up to set email alerts
|

Lie symmetry analysis of the effects of urban infrastructures on residential property values

Abstract: Due to the complexity of socio-economic-related issues, people thought of housing market as a chaotic nucleus situated at the intersection of neighboring sciences. It has been known that the dependence of house features on the residential property value can be estimated employing the well-established hedonic regression analysis method in teams of location characteristic, neighborhood characteristic and structure characteristic. However, to further assess the roles of urban infrastructures in housing markets, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 45 publications
(37 reference statements)
0
8
0
Order By: Relevance
“…The significant spatial spectrum features undoubtedly indicated that the entire price fluctuation was regulated by the Park, Transportation or both infrastructures marked on the maps. 3) is used to describe human perceptions [2,76,77]. As far as the symmetry behaviors of the house market fluctuation corresponding to the economic invariance are concerned, the special linear group structure is extended by embedding SO(3) ⊗ R(3) in SL(2, R).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The significant spatial spectrum features undoubtedly indicated that the entire price fluctuation was regulated by the Park, Transportation or both infrastructures marked on the maps. 3) is used to describe human perceptions [2,76,77]. As far as the symmetry behaviors of the house market fluctuation corresponding to the economic invariance are concerned, the special linear group structure is extended by embedding SO(3) ⊗ R(3) in SL(2, R).…”
Section: Resultsmentioning
confidence: 99%
“…Inspired by the principles of physics, many physicists have studied financial markets by assuming that the economic world behaves like a set of interacting particles [1]. Using the new tools of statistical physics and recent breakthroughs in understanding chaotic systems, physicists or statisticians, with the help of some serious mathematics borrowed from the study of disordered materials, are dismantling some of the puzzling economics and reducing them to some elegant general principles, e.g., symmetry and invariance [2]. One of the fundamental human needs is access to decent and affordable housing [3,4].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations